The relationship between epicardial fat volume and myocardial perfusion scintigraphy findings - Öncü, Süleyman; Ertürk, Seyit Ahmet (The European Research Journal, 2023)
Objectives: We investigated the epicardial fat volume (EFV) between patients with normal perfusion and reversible perfusion abnormalities in the myocardial perfusion scintigraphy (MPS) in patients with suspected coronary artery disease (CAD). In addition, we aimed to investigate the relationship of automated analysis parameters obtained in the MPS SPECT examination with EFV. Methods: A total of 295 patients (182 F, 113 M) who underwent MPS in our unit with the suspicion of CAD in the last 1 year and who had a recent thorax CT examination were included. EFV measurement in CT scans was done with Invesalius software. MPS was performed in all patients with a one-day stress and rest imaging protocol. In the stress study, imaging was performed approximately 30-45 minutes after intravenous injection of 12 mCi Tc99m Sestamibi. Rest study imaging was performed approximately 30-60 minutes after intravenous injection of 25 mCi Tc99m Sestamibi. Results: Median EFV was 53.00 ml (interquartile range: 23 ml, range 17-238 ml) in patients with normal MPS, and 62.00 ml in patients with myocardial ischemia on scintigraphy (interquartile range: 53 ml, range: 25-207 ml). The EFV value was statistically significantly higher in patients with reversible ischemia on MPS compared to patients with normal scintigraphy findings (p < 0.001). There was a statistically significant, low, and positive correlation between EFV and summed difference score (SDS) values (p = 0.002, r = 0.178). Conclusions: The EFV value was significantly higher in patients with reversible ischemia on MPS compared to patients with normal scintigraphy findings. Also there was a statistically low and positive correlation between EFV and SDS values. The automatic calculation of the EFV value during this examination may be a good additional parameter to detect the presence of ischemia.